Defect Analysis of Ceramic Products with Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA) Methods at PT. XYZ - Putri, Ananda Susyana; Aryanny, Enny (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Ceramic product company is one of the companies engaged in the ceramic industry. Ceramic product company produces various types of floor tiles with various sizes including sizes 40x40 cm, 50x50 cm, and 60x60 cm. Problems that arise at ceramic product company is that there are still defects in the 50x50 cm ceramic production line which is quite high, this certainly cannot be separated from the company's losses. Therefore, to reduce the level of defects in products, it needs to be supported by maintenance management and employee expertise. The purpose of this study is to determine product defects and propose improvements to reduce product defects. This research uses the Statistical Quality Control (SQC) method to control quality from the initial process to the finished product and Failure Mode Effect Analysis (FMEA) is used to identify and prevent problems that occur in products and processes. Based on the results of the analysis from October 2022 to March 2023, with a total production of 327,600 products, there are 56,543 defective products. Based on the results of the Pareto diagram for chipping before firing with a percentage of (34.3%), crack defects of (25.6%), chipping before vela of (21.2%), and  ink drop defects of (18.9%). The calculation of RPN for ceramic production measuring 50x50 cm obtained several risks with the highest priority level, obtained the highest RPN of 288 from the type of crack defect with a proposed improvement, which emphasizes the operator to always pay attention to the running machine settings.